Pole piece preform, pole piece and battery

By introducing a pore-forming agent into the electrode sheet prefabricated body of the lithium-ion battery, an active material layer with different porosities is formed, which solves the problem of internal concentration polarization of the electrode sheet and improves the energy density and cycle stability of the battery.

CN119627042AActive Publication Date: 2025-03-14EVE POWER CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411615680.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-03-14
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The internal concentration polarization of the electrode plate of the lithium-ion battery increases, resulting in a decrease in the cycling performance of the battery.

Method used

An electrode sheet preform is adopted, which includes a current collector, a first initial active material layer and a second initial active material layer arranged in sequence. A first pore-forming agent is dispersed in the first initial active material layer and a second pore-forming agent is dispersed in the second initial active material layer. By adjusting the content and particle size of the pore-forming agent, a first active material layer with a higher porosity and a second active material layer with a lower porosity are formed.

Benefits of technology

The transmission efficiency and kinetic performance of lithium ions are improved, the transmission resistance of the electrolyte in the second active material layer is reduced, the polarization effect in the electrode sheet is reduced, the interface reaction between the electrolyte and the active material in the electrode sheet is optimized, and the energy density and cycle stability of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627042A_ABST
    Figure CN119627042A_ABST
Patent Text Reader

Abstract

The invention provides a pole piece preform, a pole piece and a battery, and aims to solve the technical problem of concentration polarization in the pole piece. The pole piece preform comprises a current collector, a first initial active material layer and a second initial active material layer which are sequentially stacked; a first pore-forming agent with the mass content of w1 is dispersed in the first initial active material layer, and the average particle size of the first pore-forming agent is d1; a second pore-forming agent with the mass content of w2 is dispersed in the second initial active material layer, and the average particle size of the second pore-forming agent is d2; wherein # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery manufacturing, and in particular to a pole piece preform, a pole piece and a battery. Background Art

[0002] With the continuous growth of power market demand, higher requirements are placed on the energy density, fast charging and cycle performance of lithium-ion batteries. In order to improve the energy density of lithium-ion batteries, high surface density and high compaction density are usually used to improve the volume utilization of lithium-ion batteries. However, in actual manufacturing, increasing the compaction density will lead to a decrease in the porosity of the pole piece and poor electrolyte wettability, which is not conducive to the migration and diffusion of lithium ions inside the pole piece, resulting in an increase in the concentration polarization inside the pole piece and a decrease in the cycle performance of the battery. Summary of the invention

[0003] The embodiments of the present application provide a pole piece preform, a pole piece and a battery, which can improve the technical problem of concentration polarization inside the pole piece.

[0004] In a first aspect, an embodiment of the present application provides a pole piece preform, comprising a current collector, a first initial active material layer, and a second initial active material layer stacked in sequence; a first pore former having a mass content of w1 is dispersed in the first initial active material layer, and an average particle size of the first pore former is d1; a second pore former having a mass content of w2 is dispersed in the second initial active material layer, and an average particle size of the second pore former is d2;

[0005] in,

[0006] In one embodiment, the first pore-forming agent and the second pore-forming agent have the same composition, and both the first pore-forming agent and the second pore-forming agent include polymethyl methacrylate.

[0007] In one embodiment, the d1 is 1 μm to 50 μm.

[0008] In one embodiment, the d2 is 1 μm to 50 μm.

[0009] In one embodiment, the thickness of the first initial active material layer is 10 μm to 300 μm.

[0010] In one embodiment, the thickness of the second initial active material layer is 10 μm to 300 μm.

[0011] In one embodiment, the first initial active material layer further includes a first active material, a first binder and a first conductive agent; the second initial active material layer further includes a second active material, a second binder and a second conductive agent.

[0012] In one embodiment, in the first initial active material layer, the content of the first active material is 90wt% to 97wt%, the content of the first binder is 2wt% to 5wt%, the content of the first conductive agent is 0.5wt% to 7.5wt%, and the content of the first pore-forming agent is 0.1wt% to 2wt%.

[0013] In one embodiment, in the second initial active material layer, the content of the second active material is 93wt% to 98wt%, the content of the second binder is 1wt% to 5wt%, the content of the second conductive agent is 0.5wt% to 5wt%, and the content of the second pore-forming agent is 0.1wt% to 2wt%.

[0014] In one embodiment, the content of the first active material in the first initial active material layer is A1, and the content of the second active material in the second initial active material layer is A2, wherein 0.5 wt % ≤ A2 - A1 ≤ 5 wt %.

[0015] In one embodiment, the content of the first binder in the first initial active material layer is B1, and the content of the second binder in the second initial active material layer is B2, wherein 0.5wt%≤B1-B2≤3wt%.

[0016] In one embodiment, the content of the first conductive agent in the first initial active material layer is C1, and the content of the second conductive agent in the second initial active material layer is C2, wherein 0.5 wt % ≤ C2 - C1 ≤ 3 wt %.

[0017] In one embodiment, the first active material and the second active material both contain lithium iron manganese phosphate, and the chemical formula of the lithium iron manganese phosphate is: LiFe x Mn y PO4, 0<x<1, 0<y<1.

[0018] In one embodiment, the first binder and the second binder each independently include at least one of polyacrylic acid, polyvinylidene fluoride and polyvinyl alcohol.

[0019] In one embodiment, the first conductive agent and the second conductive agent each independently include at least one of conductive carbon black, carbon nanotubes, mesoporous carbon materials and vapor-grown carbon fibers.

[0020] In one embodiment, the pole piece preform further includes a bonding layer, and the bonding layer is located between the first initial active material layer and the second initial active material layer; the bonding layer includes a third bonding agent and a third conductive agent.

[0021] In one embodiment, the adhesive layer further includes a first lithium supplement agent, and the third adhesive includes a polyurethane adhesive.

[0022] In one embodiment, in the bonding layer, the content of the third bonding agent is 50wt% to 80wt%, the content of the third conductive agent is 15wt% to 40wt%, and the content of the first lithium supplement agent is 1wt% to 10wt%.

[0023] In one embodiment, the third conductive agent includes conductive carbon black and vapor-grown carbon fiber, and the content of the conductive carbon black in the third conductive agent is 80 wt % to 90 wt %.

[0024] In one embodiment, the thickness of the adhesive layer is 1 μm to 10 μm.

[0025] In one embodiment, the third binder further includes polyvinylidene fluoride; in the third binder, the content of the polyvinylidene fluoride is 30wt% to 70wt%; and / or the first lithium supplement includes lithium oxalate.

[0026] In one embodiment, the current collector includes a stacked metal layer and a lithium replenishing layer, the lithium replenishing layer is located between the metal layer and the first initial active material layer, and the lithium replenishing layer includes a fourth conductive agent, a fourth binder and a second lithium replenishing agent.

[0027] In one embodiment, in the lithium replenishing layer, the content of the fourth conductive agent is 40wt% to 85wt%, the content of the fourth binder is 5wt% to 50wt%, and the content of the second lithium replenishing agent is 0.1wt% to 10wt%.

[0028] In one embodiment, the thickness of the lithium replenishing layer is 1 μm to 20 μm.

[0029] In one embodiment, the second lithium supplement includes at least one of lithium carbonate, lithium squarate and lithium oxalate.

[0030] In one embodiment, the pole piece preform further includes an insulating layer, which covers the sides of the current collector, the first initial active material layer and the second initial active material layer and extends to an edge region of a surface of the second initial active material layer facing away from the current collector.

[0031] In one embodiment, the insulating layer includes 5 wt % to 65 wt % of the fifth binder and 35 wt % to 95 wt % of the insulating material.

[0032] In one embodiment, the thickness of the insulating layer is 1 μm to 40 μm.

[0033] In one embodiment, the insulating layer extends over a length of 1 mm to 10 mm, and a width of the insulating layer overlapping the second initial active material layer on a surface of the second initial active material layer facing away from the current collector is 1 mm to 3 mm.

[0034] In a second aspect, an embodiment of the present application provides a pole piece, which is obtained by removing the first pore-forming agent and the second pore-forming agent from the above-mentioned pole piece preform, wherein the first initial active material layer is formed into a first active material layer, and the second initial active material layer is formed into a second active material layer, and the porosity of the first active material layer is greater than the porosity of the second active material layer.

[0035] In a third aspect, an embodiment of the present application provides a battery, comprising the above-mentioned electrode.

[0036] Beneficial effects of the embodiments of the present application:

[0037] In the embodiments of the present application, since the first initial active material layer contains a first pore-forming agent and the second initial active material layer contains a second pore-forming agent, pores are formed in the first active material layer obtained after removing the first pore-forming agent from the first initial active material layer and in the second active material layer obtained after removing the second pore-forming agent from the second initial active material layer. These pores can reduce the resistance to lithium ion deintercalation and transmission in the first active material layer and the second active material layer, thereby improving the transmission efficiency and kinetic performance of lithium ions.

[0038] In addition, since the first initial active material layer is closer to the current collector than the second initial active material layer, by making the product of the mass content of the first pore former in the first initial active material layer and the average particle size of the first pore former greater than the product of the mass content of the second pore former in the second initial active material layer and the average particle size of the second pore former, the porosity of the first active material layer obtained is greater than the porosity of the second active material layer, thereby reducing the resistance to the transmission of the electrolyte in the second active material layer, improving the wetting effect of the electrolyte on the second active material layer, reducing the polarization effect in the electrode, optimizing the interface reaction between the electrolyte and the active material in the electrode, and improving the energy density and cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0040] Figure 1 is a schematic cross-sectional structural diagram of a pole piece preform provided in an embodiment of the present application;

[0041] Figure 2 is a schematic cross-sectional structural diagram of a pole piece provided in an embodiment of the present application;

[0042] Figure 3 It is a schematic diagram of the structure of the pole piece provided in the embodiment of the present application.

[0043] Reference numerals:

[0044] 1. Pole preform;

[0045] 11. current collector; 111. metal layer; 112. lithium supplement layer;

[0046] 12. a first initial active material layer;

[0047] 13. Adhesive layer;

[0048] 14. a second initial active material layer;

[0049] 15. Insulation layer;

[0050] 10. Pole piece; 101. First active material layer; 102. Second active material layer;

[0051] 100.Battery. DETAILED DESCRIPTION

[0052] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of this application.

[0053] In addition, it should be understood that the specific embodiments described herein are only used to illustrate and explain the present application, and are not used to limit the present application. In the present application, unless otherwise stated, the directional words used, such as "upper" and "lower", generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device.

[0054] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0055] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or mutual communication; it can be a direct connection, or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0056] The terms "comprises," "comprising," or any other variation thereof are intended to encompass non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements, but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus. In the absence of further limitations, an element defined by the phrase "comprising a ..." does not exclude the presence of additional identical elements in the process, method, article, or apparatus that includes the element.

[0057] In the description of the embodiments of the present application, words such as "example" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "example" or "for example" in the embodiments of the present application is not to be interpreted as being more preferred or having more advantages than another embodiment or design. The use of words such as "example" or "for example" is intended to present relative concepts in a clear manner.

[0058] To facilitate understanding of the scheme of the present application, the spline curves and arrows used in the drawings are explained here: the components indicated by the spline curves without arrows are solid components, that is, components with solid structures; the components indicated by the spline curves with arrows are virtual components, that is, components without solid structures.

[0059] First, see Figure 1 and Figure 2 The embodiment of the present application provides a pole piece preform 1, which can be made into a pole piece 10, and the pole piece 10 can be directly used in a battery 100.

[0060] Specifically, the electrode preform 1 includes a current collector 11, a first initial active material layer 12, and a second initial active material layer 14 which are stacked in sequence. Figure 1It can be seen that the first initial active material layer 12 is disposed on one side of the current collector 11, and the second initial active material layer 14 is disposed on the side of the first initial active material layer 12 away from the current collector 11. In other words, the first initial active material layer 12 is closer to the current collector 11 than the second initial active material layer 14. It should be noted here that the first initial active material layer 12 and the second initial active material layer 14 may be disposed on one side of the current collector 11, or may be disposed on both opposite sides of the current collector 11.

[0061] In detail, a first pore former is dispersed in the first initial active material layer 12, and a second pore former is dispersed in the second initial active material layer 14. The first pore former and the second pore former are added to the first initial active material layer 12 and the second initial active material layer 14, respectively. The first initial active material layer 12 and the second initial active material layer 14 can be post-processed to decompose the first pore former and the second pore former, thereby leaving holes inside the first initial active material layer 12 and the second initial active material layer 14, that is, the first initial active material layer 12 is formed as a first active material layer 101 having holes inside, and the second initial active material layer 14 is formed as a second active material layer 102 having holes inside, and the pole piece preform 1 is formed as a pole piece 10 that can be directly applied to the battery 100.

[0062] In the first initial active material layer 12, the mass content of the first pore former is w1, and the average particle size of the first pore former is d1. In the second initial active material layer 14, the mass content of the second pore former is w2, and the average particle size of the second pore former is d2. The mass content and average particle size of the first pore former in the first initial active material layer 12 and the mass content and average particle size of the second pore former in the second initial active material layer 14 satisfy the following relationship:

[0063]

[0064] It can be seen from the above relationship that the product of the mass content of the first pore former in the first initial active material layer 12 and the average particle size of the first pore former (i.e., w1d1) is 1 to 1.5 times the product of the mass content of the second pore former in the second initial active material layer 14 and the average particle size of the second pore former (i.e., w2d2). As an example, the ratio of w1d1 to w2d2 can be 1, 1.1, 1.2, 1.3, 1.4 or 1.5. Generally, the difference between w1d1 and w2d2 should not be too large, otherwise it will lead to insufficient strength of the first active material layer 101 and a decrease in the energy density of the battery 100. As an example, w1=w2, d1>d2; or, w1>w2, d1=d2; or, w1>w2, d1>d2.

[0065] In the embodiment of the present application, since the first initial active material layer 12 contains a first pore-forming agent and the second initial active material layer 14 contains a second pore-forming agent, pores are formed in the first active material layer 101 obtained after removing the first pore-forming agent in the first initial active material layer 12 and in the second active material layer 102 obtained after removing the second pore-forming agent in the second initial active material layer 14. These pores can reduce the resistance to lithium ion deintercalation and transmission in the first active material layer 101 and the second active material layer 102, thereby improving the transmission efficiency and kinetic performance of lithium ions.

[0066] In addition, since the first initial active material layer 12 is closer to the current collector 11 than the second initial active material layer 14, by making the product of the mass content of the first pore former in the first initial active material layer 12 and the average particle size of the first pore former greater than the product of the mass content of the second pore former in the second initial active material layer 14 and the average particle size of the second pore former, the porosity of the first active material layer 101 obtained in this way is greater than the porosity of the second active material layer 102, thereby reducing the resistance of the electrolyte to be transmitted in the second active material layer 102, improving the wetting effect of the electrolyte on the second active material layer 102, reducing the polarization effect in the electrode 10, optimizing the interface reaction between the electrolyte and the active material in the electrode 10, and improving the energy density and cycle stability of the battery 100.

[0067] Generally, the thickness of the first initial active material layer 12 of the pole piece preform 1 determines the thickness of the first active material layer 101 of the pole piece 10 , and the thickness of the second initial active material layer 14 of the pole piece preform 1 determines the thickness of the second active material layer 102 of the pole piece 10 .

[0068] The thickness of the active material layer in a conventional electrode should not be too large, otherwise it will lead to an increase in the concentration polarization inside the electrode. In the embodiment of the present application, by adjusting the content and particle size of the first pore-forming agent in the first initial active material layer 12, and the content and particle size of the second pore-forming agent in the second initial active material layer 14, the porosity of the first active material layer 101 can be greater than the porosity of the second active material layer 102, so that the thickness of the first initial active material layer 12 and the thickness of the second initial active material layer 14 can be further increased, thereby increasing the thickness of the first active material layer 101 and the second active material layer 102, and improving the energy density of the battery 100.

[0069] In some embodiments, the thickness of the first initial active material layer 12 is 10 μm to 300 μm. As an example, the thickness of the first initial active material layer 12 is 10 μm, 20 μm, 40 μm, 60 μm, 80 μm, 100 μm, 120 μm, 140 μm, 160 μm, 180 μm, 200 μm, 220 μm, 240 μm, 260 μm, 280 μm or 300 μm. Optionally, the thickness of the first initial active material layer 12 is 100 μm to 300 μm. By increasing the thickness of the first initial active material layer 12, it is beneficial to increase the energy density of the battery 100.

[0070] In some embodiments, the thickness of the second initial active material layer 14 is 10 μm to 300 μm. As an example, the thickness of the second initial active material layer 14 is 10 μm, 20 μm, 40 μm, 60 μm, 80 μm, 100 μm, 120 μm, 140 μm, 160 μm, 180 μm, 200 μm, 220 μm, 240 μm, 260 μm, 280 μm or 300 μm. Optionally, the thickness of the second initial active material layer 14 is 100 μm to 300 μm. By increasing the thickness of the second initial active material layer 14, it is beneficial to increase the energy density of the battery 100.

[0071] In some embodiments, the thickness of the first initial active material layer 12 is not equal to the thickness of the second initial active material layer 14. Of course, in other embodiments, the thickness of the first initial active material layer 12 and the thickness of the second initial active material layer 14 may also be equal.

[0072] In some embodiments, the first pore former and the second pore former have the same composition. This makes it easy to remove the first pore former in the first initial active material layer 12 and the second pore former in the second initial active material layer 14 through the same post-processing process to obtain the first active material layer 101 and the second active material layer 102, thereby reducing the difficulty of manufacturing the electrode 10 and facilitating the control of the porosity in the first active material layer 101 and the second active material layer 102. Of course, in other embodiments, the composition of the first pore former and the second pore former may also be different.

[0073] In some embodiments, the first pore former and the second pore former each independently include at least one of paraffin microspheres, refined naphthalene, polyethylene oxide and polymethyl methacrylate. Generally, different pore formers will result in different post-processing processes. For example, some pore formers can be removed by heat treatment to melt or decompose them into gases; while some pore formers can be removed by extraction. As an example, the first pore former is the same as the second pore former, and both the first pore former and the second pore former include polymethyl methacrylate (PMMA). Polymethyl methacrylate can be removed by extraction.

[0074] In some embodiments, d1 is 1 μm to 50 μm, that is, the average particle size of the first pore former is 1 μm to 50 μm. The average particle size of the first pore former will affect the distribution and size of the pores in the first active material layer 101. When the content of the first pore former is the same, the larger the average particle size of the first pore former, the larger the pore size of the pores in the first active material layer 101, the fewer the number of pores, the greater the distance between the pores, and the lower the continuity; the smaller the average particle size of the first pore former, the smaller the pore size of the pores in the first active material layer 101, the greater the number of pores, the smaller the distance between the pores, and the higher the continuity. As an example, d1 is 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm.

[0075] In some embodiments, d2 is 1 μm to 50 μm, that is, the average particle size of the second pore former is 1 μm to 50 μm. The average particle size of the second pore former will affect the distribution and size of the pores in the second active material layer 102. When the content of the second pore former is the same, the larger the average particle size of the second pore former, the larger the pore size of the pores in the second active material layer 102, the fewer the number of pores, the greater the distance between the pores, and the lower the continuity; the smaller the average particle size of the second pore former, the smaller the pore size of the pores in the second active material layer 102, the greater the number of pores, the smaller the distance between the pores, and the higher the continuity. As an example, d2 is 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm.

[0076] In some embodiments, the first initial active material layer 12 further includes a first active material, a first binder, and a first conductive agent; the second initial active material layer 14 further includes a second active material, a second binder, and a second conductive agent. It can be understood that the first pore former is dispersed in the first active material, the first binder, and the first conductive agent, and the first pore former is dispersed in the second active material, the second binder, and the second conductive agent. It should be noted that the first active material and the second active material may be the same or different; the first binder and the second binder may be the same or different; the first conductive agent and the second conductive agent may be the same or different. However, the first active material and the second active material are of the same type, for example, the first active material and the second active material are both positive electrode active materials, or the first active material and the second active material are both negative electrode active materials.

[0077] In some embodiments, the first active material and the second active material are the same, and both the first active material and the second active material are positive electrode active materials. Thus, the obtained electrode sheet preform 1 is a positive electrode sheet preform, and the positive electrode sheet preform can be made into a positive electrode sheet.

[0078] In some embodiments, the first active material and the second active material both include lithium iron manganese phosphate, which has the characteristics of high energy density, good stability, and low cost, and is conducive to improving the comprehensive performance of the battery 100. In detail, the chemical formula of lithium iron manganese phosphate is: LiFe x Mn y PO4, 0<x<1, 0<y<1. As an example, x is 0.001, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 0.999; y is 0.001, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 0.999.

[0079] In some embodiments, the first binder includes at least one of polyacrylic acid (PAA), polyvinylidene fluoride (PVDF), and polyvinyl alcohol (PVA). Independently, the second binder includes at least one of polyacrylic acid (PAA), polyvinylidene fluoride (PVDF), and polyvinyl alcohol (PVA).

[0080] In some embodiments, the first conductive agent includes at least one of conductive carbon black, carbon nanotubes (CNT), mesoporous carbon materials, and vapor grown carbon fibers (VGCF). Independently, the second conductive agent includes at least one of conductive carbon black, carbon nanotubes, mesoporous carbon materials, and vapor grown carbon fibers. As an example, the conductive carbon black includes at least one of acetylene black, Super P (SP), and Ketjen black. As an example, the carbon nanotube includes at least one of single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT). As an example, the mesoporous carbon material includes an ordered mesoporous carbon material CMK-3.

[0081] In some embodiments, in the first initial active material layer 12, the content of the first active material is 90 wt% to 97 wt%, the content of the first binder is 2 wt% to 5 wt%, the content of the first conductive agent is 0.5 wt% to 7.5 wt%, and the content of the first pore-forming agent (i.e., w1) is 0.1 wt% to 2 wt%. As an example, the content of the first active material is 90 wt%, 91 wt%, 92 wt%, 93 wt%, 94 wt%, 95 wt%, 96 wt% or 97 wt%; the content of the first binder is 2.0 wt%, 2.5 wt%, 3.0 wt%, 3.5 wt%, 4.0 wt%, 4.5 wt% or 5.0 wt%; the content of the first conductive agent is 0.5 wt%, 1.0 wt%, 1.5 wt%, 2.0 wt%, 2.5 ... .5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, 5.0wt%, 5.5wt%, 6.0wt%, 6.5wt%, 7.0wt% or 7.5wt%; the content of the first pore-forming agent is 0.1wt%, 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt%, 1.0wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt% or 2wt%.

[0082] In some embodiments, in the second initial active material layer 14, the content of the second active material is 93wt% to 98wt%, the content of the second binder is 1wt% to 5wt%, the content of the second conductive agent is 0.5wt% to 5wt%, and the content of the second pore former (i.e., w2) is 0.1wt% to 2wt%. As an example, the content of the second active material is 93wt%, 94wt%, 95wt%, 96wt%, 97wt% or 98wt%; the content of the second binder is 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt% or 5.0wt%; the content of the second conductive agent is 0.5wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt% or 5.0wt%; the content of the second pore-forming agent is 0.1wt%, 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt%, 1.0wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt% or 2wt%.

[0083] In some embodiments, the content of the first active material in the first initial active material layer 12 is A1, and the content of the second active material in the second initial active material layer 14 is A2, wherein 0.5wt%≤A2-A1≤5wt%. That is, the content of the second active material in the second initial active material layer 14 is higher than that in the first initial active material layer 12, which facilitates improving the energy density of the battery 100. As an example, the difference between A2 and A1 is 0.5wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt% or 5wt%.

[0084] In some embodiments, the content of the first binder in the first initial active material layer 12 is B1, and the content of the second binder in the second initial active material layer 14 is B2, wherein 0.5wt%≤B1-B2≤3wt%. That is, the content of the second binder in the second initial active material layer 14 is lower than that in the first initial active material layer 12. As an example, the difference between B1 and B2 is 0.5wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt% or 3wt%.

[0085] In some embodiments, the content of the first conductive agent in the first initial active material layer 12 is C1, and the content of the second conductive agent in the second initial active material layer 14 is C2, wherein 0.5wt%≤C2-C1≤3wt%. That is, compared with the first initial active material layer 12, the content of the second conductive agent in the second initial active material layer 14 is higher, which facilitates improving the conductivity of the second active material layer 102, especially when the content of the second active material in the second initial active material layer 14 is also higher than the content of the first active material in the first initial active material layer 12, the second conductive agent and the second active material cooperate with each other to improve the cycle performance of the battery 100. As an example, the difference between C2 and C1 is 0.5wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt% or 3wt%.

[0086] In some embodiments, the pole piece preform 1 further includes a bonding layer 13, and the bonding layer 13 is located between the first initial active material layer 12 and the second initial active material layer 14; the bonding layer 13 includes a third bonding agent and a third conductive agent. It can be understood that if the pole piece preform 1 includes the bonding layer 13, then the pole piece 10 also includes the bonding layer 13, and the bonding layer 13 is located between the first active material layer 101 and the second active material layer 102 in the pole piece 10.

[0087] Generally, during the cycle of the battery 100, the electrolyte in the battery 100 will be consumed, resulting in insufficient electrolyte, and then the cycle dive occurs. By setting the bonding layer 13, and the bonding layer 13 includes a third bonding agent and a third conductive agent, the bonding layer 13 is not only conductive but also has the characteristic of absorbing electrolyte. In this way, during the preparation of the battery 100, the bonding layer 13 can absorb a part of the electrolyte in advance and store the electrolyte. In this way, in the later stage of the cycle of the battery 100, the bonding layer 13 can form a sub-electrolyte supply source to continue to replenish the electrolyte to the first active material layer 101 and the second active material layer 102, delaying the time when the battery 100 experiences a cycle dive.

[0088] In some embodiments, the bonding layer 13 further includes a first lithium replenisher, and the third binder includes a polyurethane binder. By adding the first lithium replenisher to the bonding layer 13, the ion transmission performance of the bonding layer 13 can be effectively improved, and the third binder includes a polyurethane binder, and the functional groups such as -C=O, -NH and -COC- in the polyurethane binder are conducive to lithium ion transmission, so that the first lithium replenisher in the bonding layer 13 can replenish lithium ions to the first active material layer 101 and the second active material layer 102 on both sides of the bonding layer 13, thereby improving the quality of the interface film between the active material and the electrolyte, and improving the cycle performance of the battery 100. In addition, when the first lithium replenisher is added to the bonding layer 13, the lithium ions provided by the first lithium replenisher can be transmitted to the first active material layer 101 and the second active material layer 102 through the polyurethane binder, but the gas generated by the decomposition of the first lithium replenisher is not easy to leave the bonding layer 13, which can reduce the risk of the battery 100 swelling due to the gas production of the first lithium replenisher. In addition, the electrolyte usually contains ester solvents, and the polyurethane adhesive has a good affinity with ester solvents, which is beneficial to improving the wettability of the electrolyte and promoting the transmission of the electrolyte in the electrode 10. In particular, when the porosity of the second active material layer 102 is smaller than that of the first active material layer 101, the adhesive layer 13 can promote the electrolyte to quickly pass through the second active material layer 102 and migrate to the first active material layer 101, thereby reducing the concentration polarization in the electrode 10.

[0089] In some embodiments, the third binder further includes polyvinylidene fluoride (PVDF), and the content of polyvinylidene fluoride in the third binder is 30wt% to 70wt%. Polyvinylidene fluoride has good adhesion and can provide strong adhesion and cohesion for the bonding layer 13, so that the first active material layer 101 and the second active material layer 102 can be better combined with the bonding layer 13, thereby improving the structural stability and integrity of the pole piece 10. As an example, in the third binder, the content of polyvinylidene fluoride is 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt% or 70wt%.

[0090] In some embodiments, the polyurethane-based binder includes a waterborne polyurethane binder (WUP).

[0091] In some embodiments, the third conductive agent includes conductive carbon black and vapor-grown carbon fiber, and the content of the conductive carbon black in the third conductive agent is 80wt% to 90wt%. Conductive carbon black has good electron conductivity and liquid retention capacity, while vapor-grown carbon fiber is conducive to promoting lithium ion transmission. The two cooperate with each other to ensure the transmission of ions and electrons inside the bonding layer 13; at the same time, increasing the content of conductive carbon black in the third conductive agent can improve the liquid storage capacity of the bonding layer 13. As an example, the content of conductive carbon black in the third conductive agent is 80wt%, 81wt%, 82wt%, 83wt%, 84wt%, 85wt%, 86wt%, 87wt%, 88wt%, 89wt% or 90wt%.

[0092] In some embodiments, the first lithium supplement includes at least one of lithium carbonate, lithium squarate and lithium oxalate. Optionally, the first lithium supplement includes lithium oxalate.

[0093] In some embodiments, in the bonding layer 13, the content of the third bonding agent is 50wt% to 80wt%, the content of the third conductive agent is 15wt% to 40wt%, and the content of the first lithium supplement agent is 1wt% to 10wt%. Generally, the third conductive agent can improve the conductivity of the bonding layer 13, and the first lithium supplement agent can improve the ion transmission ability of the bonding layer 13. By adjusting the content of the third bonding agent, the third conductive agent and the first lithium supplement agent in the bonding layer 13, the bonding layer 13 can have good ion and electron transmission properties. As an example, in the bonding layer 13, the content of the third bonding agent is 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt% or 80wt%, the content of the third conductive agent is 15wt%, 20wt%, 25wt%, 30wt%, 35wt% or 40wt%, and the content of the first lithium supplement agent is 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%.

[0094] In some embodiments, the thickness of the adhesive layer 13 is 1 μm to 10 μm. The adhesive layer 13 should not be too thin, otherwise the liquid retention capacity of the adhesive layer 13 is insufficient, but the adhesive layer 13 should not be too thick, otherwise it will cause the energy density of the battery 100 to decrease. As an example, the thickness of the adhesive layer 13 is 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.

[0095] In some embodiments, the current collector 11 includes a stacked metal layer 111 and a lithium replenishing layer 112, the lithium replenishing layer 112 is located between the metal layer 111 and the first initial active material layer 12, and the lithium replenishing layer 112 includes a fourth conductive agent, a fourth binder, and a second lithium replenishing agent. The provision of the lithium replenishing layer 112 can not only improve the bonding effect between the metal layer 111 and the first initial active material layer 12, but also the second lithium replenishing agent in the lithium replenishing layer 112 can replenish the lithium ions consumed by generating an interface film between the active material and the electrolyte.

[0096] In some embodiments, in the lithium replenishing layer 112, the content of the fourth conductive agent is 40wt% to 85wt%, the content of the fourth binder is 5wt% to 50wt%, and the content of the second lithium replenishing agent is 0.1wt% to 10wt%. As an example, the content of the fourth conductive agent is 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt% or 85wt%, the content of the fourth binder is 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt% or 50wt%, and the content of the second lithium replenishing agent is 0.1wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%.

[0097] In some embodiments, the thickness of the lithium replenishing layer 112 is 1 μm to 20 μm. As an example, the thickness of the lithium replenishing layer 112 is 1 μm, 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm or 20 μm.

[0098] In some embodiments, the fourth binder includes at least one of polyacrylic acid (PAA) and waterborne polyurethane binder (WUP).

[0099] In some embodiments, the second lithium supplement includes at least one of lithium carbonate, lithium squarate, and lithium oxalate.

[0100] In some embodiments, the fourth conductive agent includes at least one of conductive carbon black, carbon nanotubes (CNTs), mesoporous carbon materials, and vapor grown carbon fibers (VGCFs).

[0101] In some embodiments, the electrode preform 1 further includes an insulating layer 15, which covers the sides of the current collector 11, the first initial active material layer 12, and the second initial active material layer 14 and extends to the edge region of the second initial active material layer 14 on the side surface facing away from the current collector 11. In the case where the electrode preform 1 further includes a bonding layer 13, the insulating layer 15 also covers the side of the bonding layer 13. That is, the insulating layer 15 covers the side region from the current collector 11 to the second initial active material layer 14, and the insulating layer 15 also covers a portion of the surface of the second initial active material layer 14, specifically the edge region of the second initial active material layer 14 on the side surface facing away from the current collector 11, and the edge region is close to the side of the second initial active material layer 14.

[0102] Generally, the sides of the first initial active material layer 12 and the second initial active material layer 14 are looser than the middle structure of the first initial active material layer 12 and the second initial active material layer 14, and are prone to burrs, powder falling and other problems. By providing an insulating layer 15 and covering the sides of the first initial active material layer 12 and the second initial active material layer 14 with the insulating layer 15, burrs, dust and the like on the sides of the first initial active material layer 12 and the second initial active material layer 14 can be covered, thereby improving the safety performance of the battery 100.

[0103] In some embodiments, the insulating layer 15 includes 5wt% to 65wt% of the fifth binder and 35wt% to 95wt% of the insulating material. As an example, in the insulating layer 15, the content of the fifth binder is 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt% or 65wt%. Optionally, the fifth binder includes polyvinylidene fluoride, and the insulating material includes a ceramic material.

[0104] In some embodiments, the thickness of the insulating layer 15 is 1 μm to 40 μm. As an example, the thickness of the insulating layer 15 is 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm.

[0105] In some embodiments, the insulating layer 15 extends for a length of 1 mm to 10 mm, and the width of the insulating layer 15 overlapping the second initial active material layer 14 on the side surface of the second initial active material layer 14 away from the current collector 11 is 1 mm to 3 mm. If the first side of the insulating layer 15 is located on the current collector 11, and the second side of the insulating layer 15 opposite to the first side is located on the second initial active material layer 14, then the length of the insulating layer 15 from the first side to the second side is the length of the insulating layer 15. As an example, the length of the insulating layer 15 is 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm or 10 mm. A portion of the insulating layer 15 extends to the side surface of the second initial active material layer 14 away from the current collector 11, and the portion overlaps with the second initial active material layer 14, and the width of the portion is the overlapping width. As an example, the overlapping width can be 1 mm, 1.5 mm, 2 mm, 2.5 mm or 3 mm.

[0106] Second, see Figure 2 The embodiment of the present application also provides a pole piece 10, which is obtained by removing the first pore-forming agent and the second pore-forming agent from the pole piece preform 1, the first initial active material layer 12 is formed into the first active material layer 101, the second initial active material layer 14 is formed into the second active material layer 102, and the porosity of the first active material layer 101 is greater than the porosity of the second active material layer 102. It can be understood that the pole piece 10 includes a current collector 11, a first active material layer 101 and a second active material layer 102 which are stacked in sequence, that is, the difference between the pole piece 10 and the pole piece preform 1 is that the pole piece 10 does not contain or substantially does not contain the first pore-forming agent and the second pore-forming agent, and the positions where the first pore-forming agent and the second pore-forming agent originally existed are formed into holes.

[0107] In some embodiments, when the pole piece preform 1 further includes a bonding layer 13 , the pole piece 10 also includes a bonding layer 13 , and the bonding layer 13 is located between the first active material layer 101 and the second active material layer 102 .

[0108] In some embodiments, when the pole piece preform 1 also includes an insulating layer 15, the pole piece 10 also includes an insulating layer 15, and the insulating layer 15 covers the sides of the current collector 11, the first active material layer 101 and the second active material layer 102 and extends to the edge area of ​​the side surface of the second active material layer 102 away from the current collector 11.

[0109] In some embodiments, when the current collector 11 includes a stacked metal layer 111 and a lithium replenishing layer 112 , the pole piece 10 also includes a metal layer 111 and a lithium replenishing layer 112 , and the lithium replenishing layer 112 is located between the metal layer 111 and the first active material layer 101 .

[0110] Third, see Figure 2 The embodiment of the present application also provides a battery 100, including the above-mentioned electrode 10.

[0111] In some embodiments, the battery 100 further includes an electrolyte, the electrolyte is soaked in the pole piece 10, the electrolyte includes a solute and a solvent, the solute is dissolved in the solvent, and the solvent includes an ester solvent. As an example, the ester solvent includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

[0112] The following is a description with reference to specific embodiments.

[0113] Example 1

[0114] S1. Please refer to Figure 1 , a first coating layer (corresponding to the lithium supplement layer 112), a second coating layer (corresponding to the first initial active material layer 12), a third coating layer (corresponding to the bonding layer 13), a fourth coating layer (corresponding to the second initial active material layer 14) and a fifth coating layer (corresponding to the insulating layer 15) are sequentially arranged on the bare aluminum foil by coating to obtain a pole piece preform, wherein:

[0115] The composition of the first coating is:

[0116] Conductive agent (including SP and CMK-3 in a mass ratio of 8:2): adhesive (PAA): lithium supplement (lithium squarate) = 70wt%: 25wt%: 5wt%; the coating thickness of the first coating is 10μm.

[0117] The composition of the second coating is:

[0118] Active material (LiFe 0.5 Mn 0.5 PO4): adhesive (PVDF): conductive agent (including CNT, SP and VGCF in a mass ratio of 3:6:1): pore former (PMMA) = 92.5wt%: 5wt%: 2wt%: 0.5wt%, the D50 particle size of the pore former is 2μm, and the coating thickness of the second coating is 100μm.

[0119] The composition of the third coating is:

[0120] Adhesive (including PVDF and WPU in a mass ratio of 1:1): conductive agent (including SP and VGCF in a mass ratio of 8:2): lithium supplement (lithium oxalate) = 60wt%: 35wt%: 5wt%, and the coating thickness of the third coating is 5μm.

[0121] The composition of the fourth coating is:

[0122] Active material (LiFe 0.5 Mn0.5 PO4): adhesive (PVDF): conductive agent (including CNT, SP and VGCF in a mass ratio of 3:6:1): pore former (PMMA) = 94wt%: 3wt%: 2.5wt%: 0.5wt%, the D50 particle size of the pore former is 1.5μm, and the coating thickness of the fourth coating is 100μm.

[0123] The composition of the fifth coating is:

[0124] Adhesive (PVDF): insulating material (ceramic) = 20wt%: 80wt%, and the coating thickness of the fifth coating layer is 5 μm.

[0125] S2. After cold pressing, the electrode preform is extracted in a dichloromethane extraction tank for 3 minutes. After extraction, it is dried in an oven at 45° C. to obtain the electrode.

[0126] Example 2

[0127] The difference from Example 1 is that the composition of the first coating is:

[0128] Conductive agent (SP+CMK-3): adhesive (PAA): lithium supplement (lithium squarate) = 68wt%: 25wt%: 7wt%.

[0129] The rest is the same as Example 1.

[0130] Example 3

[0131] The difference from Example 1 is that the composition of the fourth coating is:

[0132] Active material (LiFe 0.5 Mn 0.5 PO4): binder (PVDF): conductive agent (including CNT, SP and VGCF in a mass ratio of 3:6:1): pore-forming agent (PMMA) = 94.5wt%: 2wt%: 2.5wt%: 1wt%, the D50 particle size of the pore-forming agent is 1μm.

[0133] The rest is the same as Example 1.

[0134] Example 4

[0135] The difference from Example 1 is that the composition of the second coating is:

[0136] Active material (LiFe 0.5 Mn 0.5 PO4): binder (PVDF): conductive agent (including CNT, SP and VGCF in a mass ratio of 3:6:1): pore former (PMMA) = 92.5wt%: 4.5wt%: 2wt%: 1wt%, the D50 particle size of the pore former is 2μm.

[0137] The fourth coating layer is composed of: active material (LiFe 0.5 Mn 0.5 PO4): binder (PVDF): conductive agent (including CNT, SP and VGCF in a mass ratio of 3:6:1): pore-forming agent (PMMA) = 94wt%: 2.5wt%: 2.5wt%: 1wt%, the D50 particle size of the pore-forming agent is 1.5μm.

[0138] The rest is the same as Example 1.

[0139] Example 5

[0140] The difference from Example 1 is that the composition of the second coating is:

[0141] Active material (LiFe 0.5 Mn 0.5 PO4): binder (PVDF): conductive agent (including CNT, SP and SWCNT in a mass ratio of 3:6:1): pore former (PMMA) = 92.5wt%: 5wt%: 2wt%: 0.5wt%, the D50 particle size of the pore former is 2μm.

[0142] The composition of the fourth coating is:

[0143] Active material (LiFe 0.5 Mn 0.5 PO4): binder (PVDF): conductive agent (including CNT, SP and SWCNT in a mass ratio of 3:6:1): pore former (PMMA) = 94wt%: 3wt%: 2.5wt%: 0.5wt%, the D50 particle size of the pore former is 1.5μm.

[0144] The rest is the same as Example 1.

[0145] Example 6

[0146] The difference from Example 1 is that the composition of the fifth coating is:

[0147] Adhesive (PVDF): insulating material (ceramic) = 15wt%: 85wt%.

[0148] The rest is the same as Example 1.

[0149] Example 7

[0150] The difference from Example 1 is that the composition of the second coating is:

[0151] Active material (LiFe 0.5 Mn 0.5PO4): adhesive (PVDF): conductive agent (including CNT, SP and VGCF in a mass ratio of 3:6:1): pore former (PMMA) = 92.5wt%: 5wt%: 2wt%: 0.5wt%, the D50 particle size of the pore former is 1.5μm, and the coating thickness of the second coating is 100μm.

[0152] The rest is the same as Example 1.

[0153] Example 8

[0154] The difference from Example 1 is that the composition of the second coating is:

[0155] Active material (LiFe 0.5 Mn 0.5 PO4): adhesive (PVDF): conductive agent (including CNT, SP and VGCF in a mass ratio of 3:6:1): pore former (PMMA) = 92.5wt%: 5wt%: 2wt%: 0.5wt%, the D50 particle size of the pore former is 2.25μm, and the coating thickness of the second coating is 100μm.

[0156] The rest is the same as Example 1.

[0157] Example 9

[0158] The difference from Example 1 is that no lithium supplement agent is added to the third coating (ie, the third coating only contains PVDF+WPU).

[0159] Example 10

[0160] The difference from Example 1 is that WPU is not added to the third coating (ie, the third coating only contains PVDF+lithium supplement).

[0161] Comparative Example 1

[0162] The difference from Example 1 is that the composition of the second coating is:

[0163] Active material (LiFe 0.5 Mn 0.5 PO4): binder (PVDF): conductive agent (including CNT, SP and VGCF in a mass ratio of 3:6:1) = 92.96wt%: 5.03wt%: 2.01wt%, and the coating thickness of the second coating is 100μm.

[0164] The rest is the same as Example 1.

[0165] Comparative Example 2

[0166] The difference from Example 1 is that the composition of the second coating is:

[0167] Active material (LiFe05 Mn 05 PO4): adhesive (PVDF): conductive agent (including CNT, SP and VGCF in a mass ratio of 3:6:1): pore former (PMMA) = 94.5wt%: 2.5wt%: 2.5wt%: 0.5wt%, the D50 particle size of the pore former is 1μm, and the coating thickness of the second coating is 100μm.

[0168] The rest is the same as Example 1.

[0169] Comparative Example 3

[0170] The difference from Example 1 is that the composition of the second coating is:

[0171] Active material (LiFe 0.5 Mn 0.5 PO4): adhesive (PVDF): conductive agent (including CNT, SP and VGCF in a mass ratio of 3:6:1): pore former (PMMA) = 92.5wt%: 5wt%: 2wt%: 0.5wt%, the D50 particle size of the pore former is 2.5μm, and the coating thickness of the second coating is 100μm.

[0172] The rest is the same as Example 1.

[0173] Comparative Example 4

[0174] The difference from Example 1 is that the third coating layer is eliminated, and the rest is the same as Example 1.

[0175] Comparative Example 5

[0176] The difference from Example 1 is that the composition of the second coating is:

[0177] Active material (LiFe 0.5 Mn 0.5 PO4): binder (PVDF): conductive agent (including CNT, SP and VGCF in a mass ratio of 3:6:1) = 92.96wt%: 5.03wt%: 2.01wt%, and the coating thickness of the second coating is 100μm.

[0178] The composition of the fourth coating is:

[0179] Active material (LiFe 0.5 Mn 0.5 PO4): binder (PVDF): conductive agent (including CNT, SP and VGCF in a mass ratio of 3:6:1) = 94.47wt%: 3.02wt%: 2.51wt%, and the coating thickness of the fourth coating layer is 100μm.

[0180] The rest is the same as Example 1.

[0181] The following performance characterizations were performed:

[0182] 1. Pole tortuosity test.

[0183] The pole pieces prepared in the above examples and comparative examples were assembled into symmetrical batteries, and the electrochemical impedance spectroscopy (EIS) was tested using an electrochemical workstation, with the frequency range set to 100000 Hz to 0.1 Hz and the amplitude set to 5 mV. The measured Nyquist diagram was fitted with an equivalent circuit to obtain the ionic impedance Rion.

[0184] The tortuosity is given by the formula Calculate, where Rion is the liquid phase transmission impedance of ions in the electrode pores, A is the electrode apparent area, ε is the electrode porosity, κ is the ionic conductivity of the electrolyte, and t is the total thickness of the two electrodes. The tortuosity test results of the electrode piece are recorded in Table 1.

[0185] 2. Battery cycle performance test.

[0186] 2.1. The electrode sheets prepared in the above embodiments and comparative examples are cut and die-cut to obtain positive electrode sheets, artificial graphite is used as the negative electrode, 1M LiPF6 (EC:DEC:DMC=1:1:1, volume ratio) is used as the electrolyte, and the stacking, liquid injection, packaging and vacuum sealing processes are carried out to obtain a lithium-ion battery (specifically a soft-pack battery).

[0187] 2.2. Test the cycle capacity retention rate of lithium-ion batteries at 25°C: At 25°C, the lithium-ion batteries were subjected to a 1C / 1C cycle test with a voltage range of 2.5 to 3.65V. The capacity retention rate was calculated by dividing the capacity after 500 cycles by the initial capacity to obtain the capacity retention rate after the cycle. The test results are recorded in Table 1.

[0188] 2.3. Test the cycle capacity retention rate of lithium-ion batteries at 45°C: At 45°C, the lithium-ion batteries were subjected to a 1C / 1C cycle test with a voltage range of 2.5 to 3.65V. The capacity retention rate was calculated by dividing the capacity after 500 cycles by the initial capacity to obtain the capacity retention rate after the cycle. The test results are recorded in Table 1.

[0189] Table 1

[0190]

[0191]

[0192] As can be seen from Table 1, compared with Comparative Examples 1 and 5, the results of Examples 1 to 10 show that adding pore-forming agents to both the second coating and the fourth coating can effectively reduce the tortuosity of the pores in the electrode, making the transmission of lithium ions in the electrode easier, and improving the cycle capacity retention rate of the battery.

[0193] Further comparison of Comparative Example 1, Comparative Example 2, Example 7, Example 1, Example 8 and Comparative Example 3 shows that as The value of increases from 0 to 1.6, and the tortuosity of the pores in the electrode decreases from 3.54 to 1.72. However, the cycle capacity retention rate of the battery increases first and then decreases. This is because as As the value of increases, the tortuosity decreases, the difficulty of lithium ion transmission in the electrode decreases, and the concentration polarization inside the electrode decreases, thereby increasing the cycle capacity retention rate of the battery; however If the thickness is too large (see Comparative Example 3), the strength of the second coating layer will be reduced, which will also lead to a decrease in the cycle capacity retention rate of the battery.

[0194] Further comparison of Example 1, Example 9, Example 10 and Comparative Example 4 shows that although the tortuosity of the four is close, the cycle capacity retention rate of the battery corresponding to Example 9, Example 10 and Comparative Example 4 is reduced. This is because no lithium supplement is added to the third coating in Example 9, resulting in a decrease in the ion transport performance of the third coating, and an increase in the volume resistivity and interface resistance of the pole piece, thereby reducing the cycle capacity retention rate of the battery. In Example 10, although a lithium supplement is added, WPU is not added, which makes it difficult for the lithium ions in the lithium supplement to be transferred, so that the role of the lithium supplement cannot be well played, thereby reducing the cycle capacity retention rate of the battery. In other words, the lithium supplement and WPU can cooperate with each other to reduce the volume resistivity and interface resistance of the pole piece and improve the cycle performance of the battery. Comparative Example 4 cancels the third coating, and the cycle capacity retention rate of the corresponding battery is close to the cycle capacity retention rate of the battery corresponding to Example 9 and Example 10, further illustrating that only when the lithium supplement is added to the third coating, and the lithium ions in the lithium supplement can be effectively transferred, can the cycle performance of the battery be effectively improved.

[0195] The embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method and core idea of ​​the present application. At the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A pole piece preform, characterized in that: The invention comprises a current collector, a first initial active material layer and a second initial active material layer which are stacked in sequence; a first pore former having a mass content of w1 is dispersed in the first initial active material layer, and an average particle size of the first pore former is d1; a second pore former having a mass content of w2 is dispersed in the second initial active material layer, and an average particle size of the second pore former is d2; in, 2. The pole piece preform according to claim 1, characterized in that: The first pore-forming agent and the second pore-forming agent have the same composition, and both the first pore-forming agent and the second pore-forming agent contain polymethyl methacrylate; and / or, The d1 is 1 μm to 50 μm; and / or, The d2 is 1 μm to 50 μm; and / or, The thickness of the first initial active material layer is 10 μm to 300 μm; and / or, The thickness of the second initial active material layer is 10 μm to 300 μm.

3. The pole piece preform according to claim 1, characterized in that: The first initial active material layer further includes a first active material, a first binder and a first conductive agent; the second initial active material layer further includes a second active material, a second binder and a second conductive agent.

4. The pole piece preform according to claim 3, characterized in that: In the first initial active material layer, the content of the first active material is 90wt% to 97wt%, the content of the first binder is 2wt% to 5wt%, the content of the first conductive agent is 0.5wt% to 7.5wt%, and the content of the first pore-forming agent is 0.1wt% to 2wt%; and / or, In the second initial active material layer, the content of the second active material is 93wt% to 98wt%, the content of the second binder is 1wt% to 5wt%, the content of the second conductive agent is 0.5wt% to 5wt%, and the content of the second pore former is 0.1wt% to 2wt%.

5. The pole piece preform according to claim 3, characterized in that: The content of the first active material in the first initial active material layer is A1, and the content of the second active material in the second initial active material layer is A2, wherein 0.5wt%≤A2-A1≤5wt%; and / or, The content of the first binder in the first initial active material layer is B1, and the content of the second binder in the second initial active material layer is B2, wherein 0.5wt%≤B1-B2≤3wt%; and / or, The content of the first conductive agent in the first initial active material layer is C1, and the content of the second conductive agent in the second initial active material layer is C2, wherein 0.5 wt % ≤ C2 - C1 ≤ 3 wt %.

6. The pole piece preform according to claim 3, characterized in that: The first active material and the second active material both contain lithium iron manganese phosphate, and the chemical formula of the lithium iron manganese phosphate is: LiFe x Mn y PO4, 0<x<1, 0<y<1; and / or, The first binder and the second binder each independently include at least one of polyacrylic acid, polyvinylidene fluoride and polyvinyl alcohol; and / or, The first conductive agent and the second conductive agent each independently include at least one of conductive carbon black, carbon nanotubes, mesoporous carbon materials, and vapor-grown carbon fibers.

7. The pole piece preform according to any one of claims 1 to 6, characterized in that: The pole piece preform further includes a bonding layer, and the bonding layer is located between the first initial active material layer and the second initial active material layer; the bonding layer includes a third bonding agent and a third conductive agent.

8. The pole piece preform according to claim 7, characterized in that: The adhesive layer further includes a first lithium supplement agent, and the third adhesive includes a polyurethane adhesive.

9. The pole piece preform according to claim 8, characterized in that: In the bonding layer, the content of the third bonding agent is 50wt% to 80wt%, the content of the third conductive agent is 15wt% to 40wt%, and the content of the first lithium supplement agent is 1wt% to 10wt%; and / or, The third conductive agent comprises conductive carbon black and vapor-grown carbon fiber, wherein the content of the conductive carbon black in the third conductive agent is 80 wt% to 90 wt%; and / or, The thickness of the bonding layer is 1 μm to 10 μm.

10. The pole piece preform according to claim 8, characterized in that: The third binder further includes polyvinylidene fluoride; in the third binder, the content of the polyvinylidene fluoride is 30wt% to 70wt%; and / or, the first lithium supplement includes lithium oxalate.

11. The pole piece preform according to any one of claims 1 to 6, characterized in that: The current collector includes a metal layer and a lithium replenishing layer which are stacked, wherein the lithium replenishing layer is located between the metal layer and the first initial active material layer, and the lithium replenishing layer includes a fourth conductive agent, a fourth binder, and a second lithium replenishing agent.

12. The pole piece preform according to claim 11, characterized in that: In the lithium replenishing layer, the content of the fourth conductive agent is 40wt% to 85wt%, the content of the fourth binder is 5wt% to 50wt%, and the content of the second lithium replenishing agent is 0.1wt% to 10wt%; and / or, The thickness of the lithium supplement layer is 1 μm to 20 μm; and / or, The second lithium supplement includes at least one of lithium carbonate, lithium squarate and lithium oxalate.

13. The pole piece preform according to any one of claims 1 to 6, characterized in that: The pole piece preform further includes an insulating layer, which covers the sides of the current collector, the first initial active material layer and the second initial active material layer and extends to an edge region of a surface of the second initial active material layer facing away from the current collector.

14. The pole piece preform according to claim 13, characterized in that: The insulating layer comprises 5wt% to 65wt% of a fifth adhesive and 35wt% to 95wt% of an insulating material; and / or, The thickness of the insulating layer is 1 μm to 40 μm; and / or, The insulating layer extends over a length of 1 mm to 10 mm, and a width of the insulating layer overlapping the second initial active material layer on a surface of the second initial active material layer facing away from the current collector is 1 mm to 3 mm.

15. A pole piece, characterized in that: The pole piece is obtained by removing the first pore-forming agent and the second pore-forming agent from the pole piece preform according to any one of claims 1 to 14, the first initial active material layer is formed into a first active material layer, the second initial active material layer is formed into a second active material layer, and the porosity of the first active material layer is greater than the porosity of the second active material layer.

16. A battery, characterized in that: Comprising a pole piece according to claim 15.

Citation Information

Patent Citations

  • Carbon coated aluminum foil with lithium-replenishing function and preparation method thereof

    CN108649231A

  • Electrode pole plate and secondary battery

    CN110828826A

  • Hierarchical porous pole piece and preparation method and application thereof

    CN111490225A

  • Solid electrolyte, and lithium metal anode and a preparation method thereof

    CN112117488A

  • Lithium ion battery

    CN112421128A